2022
DOI: 10.1044/2021_jslhr-21-00367
|View full text |Cite
|
Sign up to set email alerts
|

On the Benefits of Speech-Language Therapy for Individuals Born With Cleft Palate: A Systematic Review and Meta-Analysis of Individual Participant Data

Abstract: Purpose: Cleft lip and/or palate (CLP) is a common birth defect, and after reconstructive surgery, about 50% of children at 5 years of age have speech deviations and are referred to speech-language therapy (SLT). The peer-reviewed evidence for the benefit of SLT has been uncertain. Our objective was to systematically review and meta-analytically summarize the benefit of SLT for individuals born with CLP. Method: A systematic search was conducted (last s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…Patients with noncleft VPI had longer velum and longer lift times. This matches with what we see clinically, as noncleft VPI cases have not had surgery on their palate and tend to have more typical structural and muscular anatomy as their VPI may be neurological in nature 7,11 . Sustained closure during /s/ had moderate inter-rater reliability.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Patients with noncleft VPI had longer velum and longer lift times. This matches with what we see clinically, as noncleft VPI cases have not had surgery on their palate and tend to have more typical structural and muscular anatomy as their VPI may be neurological in nature 7,11 . Sustained closure during /s/ had moderate inter-rater reliability.…”
Section: Discussionsupporting
confidence: 82%
“…It is well understood that speech therapy intervention is required to correct the articulation and phonological components of the disordered speech of individuals identified as having “CP speech,” 11–13 however, the components of speech related to VPI, including hypernasal resonance and abnormal nasal air emission, often require surgical consideration to improve the speaker’s ability to achieve VP closure.…”
mentioning
confidence: 99%
“…However, Sand et al. (2022) concluded that many individuals benefit from speech therapy, even though less than a third of the individuals’ speech production reached the level of their peers after speech therapy. Therefore, it is important to control for the number of speech therapy visits across arms and trials.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence should not necessarily include randomized controlled trials with large sample sizes. A recently published systematic review and meta‐analysis called for more research on the individual level with an eye on considering clinically relevant improvements rather than statistical significance (Sand et al., 2022). This call opens some interesting perspectives for SLPs who are active in clinical practice.…”
Section: Discussionmentioning
confidence: 99%